THEORETICAL STUDY OF THE VIBRATION OF CHAIN NETWORKS - Turdaliev, Voxidjon; Akbarov, Abduraxmon; Toychieva, Majuda (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article presents the results of theoretical studies of oscillations of the free branch of the chain of a chain transmission with a variable interaxial distance. In the studies, the free branch of the chain was isolated separately and studied as a single-mass mechanical system. As a result of the studies, an equation of motion of the free branch of the chain was compiled and, based on the numerical solution, the laws of change and graphical dependence were constructed.